Réponses

2014-01-14T12:30:39+01:00
A=(-3x+2)(2x+5)+3(2x²+7x)

A= (-3*74.2752+2)(2*74.2752+5)+3(2*74.2752²+7*74.2752)
A=  (-222.8256+2)(148.5504+5) + 3(11033.6107+519.9264)
A=       -220.8256*153.5504      + 3*11553.5371
A=              -33907.859            +  34660.6113
A=                                    752.7523
2014-01-14T12:42:59+01:00
Développer et réduire A=(-3x+2)(2x+5)+3(2x²+7x)

A=(-3x+2)(2x+5)+3(2x²+7x)
A=(-3x+2)(2x+5)+(6x²+21x)
A=(-6x²-15x +4x+10)+(6x²+21x)
A= 10x +10

Calculer A pour x=74,2752
A=10x +10
A= 10 (74,2752)² +10
A=742,752 + 10
A = 752,752